Analysis And Design Computer Device Web-Based Sales Application At CV. DATA BARU - Anugraha, Muh Redha; Sulistiowati, Sulistiowati; Kusumawati, Weny Indah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract:  The selling process of computers in CV. Data Baru currently ongoing manually. So far the sale of computers in CV. Data Baru can be done directly or indirectly. For the direct sale customers can come directly to the store, while for the sales are not directly usually customers ordered the stuff by telephone and email.The impact to the customers who are derived from out of town have to wait to certainty whether there were any supplies of ordered computer. Catalog computer information also could not be known directly by customers. CV. Data Baru need an application that can do the computer selling process. Application designed is expected to ease CV. Data Baru in the online computer selling process. Application designed to produces information report sales of computer, payment customers report, and reports supplies computers.